The role of pupils in developing student teachers' knowledge of teaching. Issue 4 (8th August 2021) - Dickerson, Claire; Levy, Roger; Jarvis, Joy; Thomas, Kit
ABSTRACT: Teachers' personal understanding of knowledge and how it is acquired has important implications for their approaches to teaching and engaging pupils in learning. This article extends learning about emergent teachers' professional knowledge by critiquing and theorising survey responses detailing student teachers' experience of teaching during their first and last placements in primary classrooms. These members of a cohort of 120 students on a new BEd degree programme in Malaysia were taught to use action (active learning), reflection and modelling (ARM) in their teaching. A keyword search of the students' accounts is used to examine the way they refer to knowledge and describe how knowledge is acquired. Four of the students' narratives are also analysed in depth using a novel 'Eraut-Shulman teacher knowledge framework', which integrates the expositions of Eraut on different types of knowledge and of Shulman on the knowledge base of teaching. The findings contribute to understanding the role of pupils in developing student teachers' knowledge of teaching and the interrelationship between the personal knowledge of teachers and pupils. In particular, it raises questions about developing 'pathic knowledge', conceptualised by van Manen, which is particularly pertinent in settings in which emphasis is placed on socially mediated learning.